1990
DOI: 10.1017/s0022216x00020952
|View full text |Cite
|
Sign up to set email alerts
|

Unlikely Transitions to Uncertain Regimes? Democracy without Compromise in the Dominican Republic and Ecuador

Abstract: Charting the historical paths to democracy has been a long-standing concern of political sociology.1 With the demise of authoritarian rule in Latin America over the last decade, a classic question of the genre has resurfaced: are there certain developmental sequences that are more likely to produce successful transitions to democracy? If there is any conclusion to be drawn from recent experiences, the answer is no. Highly heterogeneous circumstances have produced Latin America's most recent wave of democratisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…It should be noted, however, that despite gaining social inclusion black migrants remained politically marginalized. The state remained under the control of foreign capital or under elite-led exclusionary regimes for much of the twentieth century (Conaghan and Espinal 1990). …”
Section: Nation-buildingmentioning
confidence: 99%
“…It should be noted, however, that despite gaining social inclusion black migrants remained politically marginalized. The state remained under the control of foreign capital or under elite-led exclusionary regimes for much of the twentieth century (Conaghan and Espinal 1990). …”
Section: Nation-buildingmentioning
confidence: 99%
“…It faced both an entrepreneurial revolt against extreme free-market policies and mass threat from below was low Conaghan and Espinal, 1990). Similar evidence exists for the cases of Argentina, Brazil, Mexico, and Venezuela Cardoso, 1986;.…”
Section: Businessmen Landowners Pragmatic Neoliberalism and Mass Momentioning
confidence: 59%
“…Research on Ecuador, Peru, Bolivia, and the Dominican Republic showed that business elites supported a shift from authoritarianism to more democratic rule because they believed they would have greater access to the economic policymaking process under conditions in which the perceived SILVA: CAPITALIST REGIME LOYALTIES IN CHILE SILVA: CAPITALIST REGIME LOYALTIES IN CHILE SILVA: CAPITALIST REGIME LOYALTIES IN CHILE SILVA: CAPITALIST REGIME LOYALTIES IN CHILE SILVA: CAPITALIST REGIME LOYALTIES IN CHILE threat from below was low Conaghan and Espinal, 1990). Similar evidence exists for the cases of Argentina, Brazil, Mexico, and Venezuela Cardoso, 1986;.…”
Section: Democratzca (Ad)mentioning
confidence: 99%
“…En esa línea, dicha reforma constitucional fue observada por las pocas agrupaciones ciudadanas existentes como el mecanismo idóneo para liberarse de los aparentes constreñimientos que implicaba ser afiliado a un partido político. No obstante, el problema de fondo se hallaba en la ausencia de organizaciones cívicas lo suficientemente consolidadas y con plataformas definidas (Conaghan y Espinal, 1990;944 Menéndez-Carrión, 1988). 4 Lo antes expuesto se reflejó en los subsiguientes procesos electorales, en los que si bien formalmente algunos movimientos ciudadanos llegaron a ocupar espacios en la legislatura, lo que realmente sucedió fue que los caudillos provinciales o locales organizaron su agenda de gobierno utilizando el membrete de "movimientos ciudadanos".…”
Section: Asociación Cívica E Institucionalización Partidista: Una Perunclassified